Hepatitis B Virus-Specific CD8+ T Cells Maintain Functional Exhaustion after Antigen Reexposure in an Acute Activation Immune Environment - Wang, Qin; Pan, Wen; Liu, Yanan; Luo, Jinzhuo; Zhu, Dan; Lu, Yinping; Feng, Xuemei; Yang, Xuecheng; Dittmer, Ulf; Lu, Mengji; Yang, Dongliang; Liu, Jia (Frontiers in Immunology, 2018)
Chronic hepatitis B virus (HBV) infection is characterized by the presence of functionally exhausted HBV-specific CD8+ T cells. To characterize the possible residual effector ability of these cells, we reexposed CD8+ T cells from chronically HBV replicating mice to HBV antigens in an acute activation immune environment. We found that after transfer into naive mice, exhausted CD8+ T cells reexpanded in a comparable magnitude as naive CD8+ T cells in response to acute HBV infection, however, their proliferation intensity was significantly lower than that of CD8+ T cells from acute-resolving HBV replicating mice. The differentiation phenotypes driven by acute HBV replication of donor exhausted and naive CD8+ T cells were similar, but were different from those of their counterparts from acute-resolving HBV replicating mice. Nevertheless, exhausted CD8+ T cells maintained less activated phenotype, an absence of effector cytokine production and poor antiviral function after HBV reexposure in an acute activation immune environment. We thus conclude that exhausted CD8+ T cells undergo a stable form of dysfunctional differentiation during chronic HBV replication and switching immune environment alone is not sufficient for the antiviral functional reconstitution of these cells.